Enhancing heterologous expression of a key enzyme for the biosynthesis of 2′‐fucosyllactose. (30th March 2022) - Liu, Wenxian; Tang, Shizhe; Peng, Jing; Pan, Lina; Wang, Jiaqi; Cheng, Haina; Chen, Zhu; Wang, Yuguang; Zhou, Hongbo
Abstract: BACKGROUND: 2′‐Fucosyllactose (2′‐FL) is the most abundant human milk oligosaccharide (HMO) in human milk and has important physiological functions. The market demand of 2′‐FL is continuing to grow, but high production cost has limited its availability. To solve the dilemma, biosynthesis of 2′‐FL has been proposed and is considered the most promising pathway for massive production. α‐1, 2‐Fucosyltransferase is one of the key elements involved in its biosynthesis, but the limited intracellular accumulation and unstable properties of α‐1, 2‐fucosyltransferases when expressed in host strains have become a major hurdle for the effective biosynthesis of 2′‐FL. RESULTS: A combinatorial engineering strategy of synergic modification of ribosome binding site, fusion peptide and enzyme gene was leveraged to enhance the soluble expression of α‐1, 2‐fucosyltransferases and promote enzyme activity. The preferable combination was to employ an optimized ribosome binding site region to drive 3 × FLAG as a fusion partner along with the α‐1, 2‐fucosyltransferase for expression in Escherichia coli (DE3) PlySs, and protein yield and enzyme activity were remarkably improved by 11.51‐fold and 13.72‐fold, respectively. CONCLUSION: After finely tuning the synergy among different elements, the abundant protein yield and high enzyme activity confirmed that the drawbacks of heterologous expression in α‐1, 2‐fucosyltransferase had been properly addressed. A suitable external environment further drives the efficient synthesis of α‐1, 2‐fucosyltransferases. To our knowledge, this is the first report of a systematic and effective modification of α‐1, 2‐fucosyltransferase expression, which could potentially serve as a guideline for industrial application. © 2022 Society of Chemical Industry.